2020
DOI: 10.1101/2020.08.15.252353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High titers of multiple antibody isotypes against the SARS-CoV-2 spike receptor-binding domain and nucleoprotein associate with better neutralization

Abstract: Understanding antibody responses to SARS-CoV-2 is indispensable for the development of containment measures to overcome the current COVID-19 pandemic. Here, we determine the ability of sera from 101 recovered healthcare workers to neutralize both authentic SARS-CoV-2 and SARS-CoV-2 pseudotyped virus and address their antibody titers against SARS-CoV-2 nucleoprotein and spike receptor-binding domain. Interestingly, the majority of individuals have low neutralization capacity and only 6% of the healthcare worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…To characterize the prevalence of antibody response to the ACE2IS in COVID-19 patients, we performed binding analysis of 94 convalescent serum samples [14] from healthcare workers who showed PCR-positivity for COVID-19. In this experiment, we measured the IgG binding to the RBD in the absence and presence of excess soluble RBD-T competitor.…”
Section: Analysis Of Convalescent Serum Using Rbd-tmentioning
confidence: 99%
See 2 more Smart Citations
“…To characterize the prevalence of antibody response to the ACE2IS in COVID-19 patients, we performed binding analysis of 94 convalescent serum samples [14] from healthcare workers who showed PCR-positivity for COVID-19. In this experiment, we measured the IgG binding to the RBD in the absence and presence of excess soluble RBD-T competitor.…”
Section: Analysis Of Convalescent Serum Using Rbd-tmentioning
confidence: 99%
“…Serum samples were collected from 94 Healthcare workers from NYU Langone Health who showed PCR-positive for COVID-19, as reported previously [14]. All patients gave written consent for this study and all samples were de-identified by following IRB #i20-00595.…”
Section: Serum Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize the prevalence of antibody response to the ACE2IS in COVID-19 patients, we performed binding analysis of 94 convalescent serum samples 17 from healthcare workers who showed PCR-positivity for COVID-19. In this experiment, we measured the IgG binding to the RBD in the absence and presence of excess soluble RBD-T competitor.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, a number of studies of SARS-CoV-2 specific antibody responses in COVID-19 patients have revealed that, although most convalescent plasmas from COVID-19 patients contain antibodies targeting the spike protein and the RBD, they have low neutralization activity. 16 , 17 , 18 Thus, analysis of the immunogenic surfaces, or the “immunogenicity landscape”, of the spike protein and the RBD in terms of eliciting high-affinity antibodies should provide important insights into the antibody response to COVID-19 as well as vaccine design, because the spike protein and the RBD are the antigens in most first-generation vaccines for COVID-19 ( https://www.who.int/publications/m/item/draft-landscape-of-covid-19-candidate-vaccines ).…”
Section: Introductionmentioning
confidence: 99%